Characterizing the volatile compounds of different sorghum cultivars by both GC-MS and HS-GC-IMS. (February 2021) - Fan, Xiaojing; Jiao, Xin; Liu, Jinguang; Jia, Meng; Blanchard, Chris; Zhou, Zhongkai
Graphical abstract: Highlights: Hexadecanoic acid ethyl ester was highest in esters compounds for raw sorghum. Cooking led to form more fatty aldehydes with varietal dependent manner. 2-pentylfuran was one of key volatile compounds, particularly in cooked sorghum. OAV plus ANOVA was performed to characterize volatile compounds profile. Abstract: The current study applied both GC-MS and GC-IMS for characterizing the volatile compounds of six Australian sorghum cultivars. For raw sorghum, the result of GC-MS showed that the ester compounds were abundant in six raw samples. Among these esters, the content of hexadecanoic acid ethyl ester was highest in all of the raw samples. Compound 3-octanone only existed in Apollo, Bazley and Liberty, and 2-undecanone was found to be in MR43. The result of GC-IMS showed that the signals of benzaldehyde, 2, 3-butanedione were generally noted in the six raw samples. In general, The Apollo and Buster had more volatile compounds, followed by Bazley and Liberty. In contrast, MR43 and G44 had the least volatile compounds. For cooked sorghums, more fatty aldehydes are formed compared to its corresponding raw sample, in which the current data indicated that 40 volatile compounds were identified by GC-MS, and 11 of them were identified as the key aroma compounds (OAVs > 1). More important, the variation in the compounds of hexanal, heptanal, octanal, 2-heptenal, nonanal, trans- 2-octenal, benzeneaceldehyde, (E)-2-nonenal, 1-octen-3-ol, 1-pentanol, 2-methoxy-4-vinylphenol and 2-pentylfuran might be applied for explaining the aroma characteristics among the six sorghum cultivars. The result of GC-IMS showed that 26 volatile compounds but not in the results from GC-MS detection, indicating the advantage of the methodology combination for a better understanding the impact of cultivars and cooking on volatile characteristics of the sorghums.